The Relationship Between Adversity Quotient and Learning Motivation on Islamic Junior High School Students - Miftakhul Nur Refizal; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of education problems in Indonesia. Indonesian students' learning motivation is ranked 63 out of 72 countries. This research was conducted at Sedati Islamic Junior High School. Researchers found students who lacked motivation to learn. This type of research is quantitative with a correlational approach. The independent variable is adversity quotient as and the dependent variable is learning motivation. The total population is 128 students, with a sample of 128 students taken using the Saturated Sample technique. Data collection techniques in this study used a psychological scale Likert scale model, namely the Adversity Quotient scale and the Learning Motivation scale. The hypothesis of this research is that there is a positive relationship between Adversity Quotient and the learning motivation of junior high school students. Data analysis was carried out using Spearman's Product Moment correlation technique using the SPSS 21.0 program. The results of the analysis of the correlation coefficient of 0.632 with a significance of 0.000 <0.05. This means that there is a positive relationship between Adversity Quotient and student learning motivation. The effective contribution of the Adversity Quotient variable is 39.5% to student learning motivation.